An examination of the social perceptions and vaping preferences of young electronic nicotine delivery system users - Davidson, Myles; Al-Hamdani, Mohammed (Frontiers in Public Health, 2023)
Background Little research has been conducted on social aspects and preferences of electronic nicotine delivery system (ENDS) use among young ENDS users, and none have examined differences in these aspects and preferences by gender and tobacco use status. Methods A total of 558 young regular vapers (ages 16–24; vaped at least once a week for the last 3 months) from Nova Scotia were recruited to complete a demographic and vaping questionnaire. A 2 x 3 study design was used to compare participants on social aspects and vaping preferences based on gender (male or female) and tobacco use status (never, former, or current smoker). Chi-square tests were used to determine significant differences, and Bonferroni tests were used to assess over- and under-representation within significant variables. Results Current tobacco-using male vapers had a higher frequency of experiencing pressure to vape from friends and current employment as compared to females. Former and never tobacco-using male vapers had a higher frequency of parental awareness of their vaping behavior than females. Former tobacco-using female vapers had a higher frequency of being influenced to vape by others they know on social media than males. Both never and former tobacco-using females reported a higher frequency of exposure to vaping content on social media than males. Never tobacco-using female vapers preferred vape pen devices relative to males. Conclusions Important gender differences by tobacco use status exist and demonstrate differential patterns of social influence for ENDS use and their experiences within this demographic.